Eco-Pesantren Management: Harmonizing Islamic Values and Environmental Conservation in Traditional Educational Institutions - Akhmad Saikhu; Akhmad Baiquni; Muhammad Khoirul Lutfi (Assyfa Journal of Islamic Studies, 2025)
Environmental degradation and climate change necessitate a shift toward sustainable educational models that integrate moral and spiritual values. This study aims to analyze the implementation of the Eco-Pesantren management model at Pondok Pesantren Mambaul Hikam Jombang as a strategy to harmonize Islamic doctrines with environmental conservation efforts. Using a qualitative case study approach, data were gathered through observations of institutional policies and documentation of participatory environmental activities. The results indicate that the institution successfully integrates "Green Deen" principles through four strategic pillars: environmental policy formulation, human resource development in ecology, curriculum integration (PRLH), and participatory actions such as eco-enzyme production, waste management using 3R methods, and "plastic waste alms". The study found that this management model not only fosters ecological awareness among students (santri) but also transforms the pesantren into a center for community environmental education. In conclusion, the harmonization of Islamic values—such as Khalifah (stewardship) and Rahmatan lil’alamin—with structured ecological management provides a sustainable framework for traditional institutions to address modern environmental challenges. This model offers a replicable prototype for integrating spiritual ethics into practical conservation initiatives within the Islamic educational landscape